If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 10 + x = 0 Reorder the terms: 10 + -2x + x = 0 Combine like terms: -2x + x = -1x 10 + -1x = 0 Solving 10 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| -4u+(-5)+(-u)+(-2)= | | ln(3x)/ln(3)=3 | | (12/5)^(5/3) | | f(x)=-2x^2-4x+5 | | 8ln(8x)=24 | | 10w-2u+6u+3w= | | 0=6/7X-21 | | x^2-4x+a=(x-1)(x+b) | | -20x+4u-12u-8x= | | 5x+9y=62 | | 410x=400x+100000 | | 7-(-4t)=4t-21t | | (2x^-1y^-4z^-7/10x^-2y^-6z)^-1 | | 30+b=50 | | 12x100/2= | | 625000-37000=0 | | -3=-3/10-w | | 66+6x=71+5x | | 75+6x=83+5x | | 3y-6x+3=0 | | p*o*o*p=1 | | po=op | | 3ln(8-x)-x=0 | | oranges=ap^2les | | ln(4)=x | | ln(4)=2 | | -8sint+8cost= | | 6x^2+26x+95=0 | | 6x^2*6x+26x+95=0 | | -x^2-4x+46=0 | | 6x*6x+26x+95= | | 6*6+26x+95=0 |